Energy performance and cost analysis of phase change materials with different melting temperature in heating systems / Mehdi Rezaei - Mehdi , Rezaei (2012)
Usage of thermal energy storage (TES) for storing energy is a favorable technology which is used in current years. It improved extremely during previous years by application of phase change materials (PCMs). One of the major applications of the storage is heating and cooling in the buildings. The normal TES for application in buildings is water which is used in the heating system but recently PCM technology improvement helpd to use different types of PCMs for increasing energy and exergy efficiency of TES system. In some researches the energetic and exergetic analyses of systems which work with PCMs in fixed Melting temperature has been investigated. In present work the effect of different PCMs with different melting temperatures on the energy and exergy efficiencies is investigated by considering the price of energy, exergy and each PCM type. Change of melting temperature causes different energy and exergy efficiency and according to different properties of PCMs the mass of storage material will change and leads to different total life cycle cost. The cost of lost energy and destroyed exergy is calculated for each PCM type in their life cycle and their share in total life cycle cost sketched as a circle diagram to show their importance. It is concluded that the role of exergy in each melting temperature is more important than energy and price of PCM. The amount of average lost exergy cost share is about 70.49%, average lost energy cost share is about 29.45% and average PCM price share is about 0.06% which means for having more optimum PCM choosing, the exergy concept have more significant role in choosing melting temperature of PCM than energy and price of PCM. Keywords: Energy; Exergy; Phase change material; PCM; Economic Analyze; Solar heater;